Dream*hoping memory into futureS: reading resistant narratives about Maafa by employing futureS as a category of analysis. Issue 1 (2nd January 2017) - Arndt, Susan
ABSTRACT: This article conceptualizes "FutureS" as a category of analysis, insisting on four semantic pillars that induce me to speak of "futureS" rather than "the future". The capitalized "S" in both FutureS and futureS suggests that "future" does not exist in the (simplicity of any) singular, and this is largely due to three reasons: First, the "S" refers to the fact that futureS are causally intersected with both the past and the present. Second, it draws attention to the fact that futureS are intersected and molded by complexities and coexistences of glocal encounters of conflicting, competing, and complementary agencies, interests, contingencies, possibilities and options in the un/making and (not) sharing of futureS. Consequently, and third, futureS are made (as guided by agencies in power) and can be un*made (through resistance). In fact, agency is power's most virulent protagonist and antagonist at the very same time. This article will discuss agencies and their being triggered by dreams and hopes – and the memories they are pillared on. Delving into this thesis, this article compares two well-known conceptualizations of the integrative and causal intersection of past, memory and futureS: The German philosopher Walter Benjamin's "Angel of History" and the Adinkra philosophy of "Sankofa". Thus framed, the article analyzes fictional and factual representations of memory-driven dream*hopes. First, Martin Luther King Jr.'s "I Have a Dream" speech will be compared with J. Cole's hip-hop rereading of Black dreams against the backdrop of contemporary racial profiling in his song "Be Free". Subsequently, the article delves comparatively into negotiations of Maafa with respect to the power of memory and dream*hopes in Audre Lorde's "A Litany for Survival" and Fred D'Aguiar's The Longest Memory .